The Influence of Price, Service Quality and Promotion on Purchasing Decisions of Honda Scoopy Motorcycles at Wahana Jatake Tangerang - Likan Susanto; Widi Dewi Ruspitasari; Moh Bukhori (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
One of the products produced by the brand Honda is Honda Scoopy. This product has a unique and modern design for young people who want to look stylish and trendy. Currently, the sales of Honda Scoopy are continuously increasing and the consumer interest in this motorcycle is very high, resulting in customers having to wait for each purchase.The purpose of this research is to analyze the influence of Price, Service Quality, and Promotion on the purchasing decision of Honda Scoopy at Wahana Jatake Tangerang. The research population includes all buyers of Honda Scoopy motorcycles at Wahana Jatake located at Jalan Gatot Subroto km 8, Jatiuwung, Tangerang, during the period of April to June 2023. The research sample consists of 100 respondents using accidental sampling technique. The data analysis technique used multiple linear regression and hypothesis testing using t test and F test. The research findings indicate that 1) there is a significant influence of price on the purchasing decision of Honda Scoopy at Wahana Jatake, 2) there is a significant influence of service quality on the purchasing decision of Honda Scoopy at Wahana Jatake, 3) there is a significant influence of promotion on the purchasing decision of Honda Scoopy at Wahana Jatake, 4) Price, service quality, and promotion have a simultaneous effect on the purchasing decision of Honda Scoopy at Wahana Jatake.